Buschke-Löwenstein tumor (giant condyloma acuminatum) successfully treated by topical photodynamic therapy: a case report - Gong-Yau Chu; Tommy Chih-Chieh Chang; Chung-Hsing Chang (Wolters Kluwer Medknow Publications, 2013)
Giant condyloma acuminatum (Buschke-Löwenstein tumor) is a rare sexually transmitted disease caused by human papilloma virus infection in the anogenital area. It is characterized by rapid growth, large size, local destruction, lack of spontaneous resolution, poor response to conservative therapy (e.g., cryotherapy), and a high recurrence rate. Treatment of such tumors remains challenging. We report the case of a 56-year-old Taiwanese man with a 9-month history of the Buschke-Löwenstein tumor with rectal invasion, treated by topical photodynamic therapy. We applied 16% methyl aminolevulinate for 3 hours and irradiated the tumor with 630-nm light at a dose of 37 J⁄cm2 every 4-6 weeks. After three therapy sessions, the tumor disappeared without any scar or anal function impairment. Remote lesions that had been identified in the rectum also disappeared. Pain was the main side effect during treatment, but it was controlled by oral gabapentin. No recurrence was noted at 12-month follow-up or to date.